Analisis Hubungan Kualitas Pelayanan Kefarmasian Dengan Kepuasan Pasien Rawat jalan di Rumah Sakit Grandmed Lubuk Pakam Metode Mix Methode Tahun 2021 - Pintata Sembiring (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2022)
Patient satisfaction is the main key to the success of services that affect satisfaction in pharmaceutical services. If the service is in accordance with expectations, of course the quality of service is considered good and satisfying, on the other hand, the service received is not satisfactory, the quality of service is considered bad. The purpose of this study was to analyze the relationship between physical evidence, reliability, responsiveness, assurance, and empathy to the satisfaction of outpatients at the general hospital in Sembiring. This type of research used mix methods with cross sectional design in quantitative research and sequential explanatory strategies in qualitative research. The total population of 336 people, with a sample size of 73 people obtained using purposive sampling. Collecting data in quantitative research by distributing questionnaires while in qualitative research by means of indept interviews. The results showed that variables related to outpatient satisfaction at Grandmed Hospital were: physical evidence (p value = 0.002), reliability (p value = 0.012), responsiveness (p value = 0.003), assurance (p value = 0.010), and Empathy (p value = 0.000). It is recommended to the Grandmed Hospital Outpatient Pharmacy to maintain the good quality of service and continue to improve the quality of service to patients.